The Effects of Simvastatin on Proteinuria and Renal Function in Patients with Chronic Kidney Disease - Bancha Satirapoj; Anan Promrattanakun; Ouppatham Supasyndh; Panbuppa Choovichian (International Journal of Nephrology)
Current data suggests that statins might have beneficial effects on renal outcomes. Beneficial effects of statin treatment on renal progression in advanced chronic kidney disease (CKD) are obviously controversial. In a retrospective, controlled study, the authors have evaluated the effects of 53-week treatment with simvastatin, versus no treatment on proteinuria and renal function among 51 patients with CKD stages III-IV. By the end of the 53-week treatment, urine protein excretion decreased from 0.96 (IQR 0.54, 2.9) to 0.48 (IQR 0.18, 0.79) g/g creatinine (P<0.001) in patients treated with simvastatin in addition to ACEI and ARBs, while no change was observed among the untreated patients. Moreover, a significantly greater decrease in urine protein excretion was observed in the simvastatin group as compared with the untreated group. The mean changes of serum creatinine and eGFR did not significantly differ in both groups. A significantly greater decrease in total cholesterol and LDL-cholesterol was found in the simvastatin group than in the untreated group. In summary, apart from lipid lowering among CKD patients, ingesting simvastatin was associated with a decrease in proteinuria. These statin effects may become important for supportive therapy in renal damage in the future.